Kembalinya Kak Jun: Pengalaman Penghijrahan Seorang Mak Nyah (Jurnal Pembangunan Sosial, 2018)
This article is about a life story of a Muslim individual who has experienced gender identity disorder and follows his journey back to the Islamic way of life. Going by the nickname of â€œKak Junâ€, he has been experienced gender identity disorder since primary school, which has led him to deviate from the Shariâ€™a law. from middle school to adulthood. Kak Jun has now completely returned to the Shariâ€™ah compliant lifestyle, and he is actively preaching to the transgender community. This study focuses on the factors that motivate Kak Jun to work towards returning to a pattern of sharia-compliant life. These factors can be used to help counselors formulate effective Islamic approaches to helping these special populations be either at the level of development, prevention or recovery.